Hydrophobic composite material, preparation method thereof and application of hydrophobic composite material in 3D printing silicone rubber
The hydrophobic composite material prepared by using a one-step continuous spray-drying method in 3D printed silicone rubber is solved, and a high-performance 3D printed silicone rubber is achieved, suitable for thermal management and electromagnetic wave absorption.
Patent Information
- Application Number
- CN202411628032.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to effectively disperse two-dimensional layered materials in 3D printed silicone rubber, resulting in high viscosity of printing ink, easy to clog the needle, and affect the mechanical properties of silicone rubber.
The hydrophobic composite material is prepared by a one-step process of continuous spray-drying, and the distribution of silica between the surface and/or sheets of the two-dimensional layered material is used to avoid stacking of the two-dimensional layered material and agglomeration of silica, thereby improving its dispersion and compatibility in the silicone rubber matrix.
It realizes the low viscosity and printability of hydrophobic composite materials, improves the thermal conductivity, electromagnetic wave absorption performance and mechanical strength of 3D printed silicone rubber, and is suitable for the fields of thermal management and electromagnetic wave absorption.
Smart Images

Figure CN119505368A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and in particular relates to a hydrophobic composite material and a preparation method thereof, and an application thereof in 3D printing silicone rubber. Background Art
[0002] With the rapid development of communication technology and digital devices, electromagnetic radiation pollution and heat dissipation problems are becoming increasingly serious, which not only damages human health, but also interferes with the normal operation of electronic equipment. Therefore, the development of flexible composite materials with excellent thermal management and electromagnetic wave absorption properties has important application value in modern electronic engineering and medical equipment.
[0003] Silicone rubber elastomer is a linear polysiloxane with good mechanical properties, excellent chemical stability and flexibility, electrical insulation and high and low temperature resistance. It is often used as a matrix for flexible composite materials. Typical silicone rubber elastomers include polydimethylsiloxane (PDMS). The main chain of PDMS is composed of Si-O-Si bonds and the side groups are dimethyl. PDMS has the characteristics of high biocompatibility and low environmental harm. However, silicone rubber itself has poor heat transfer and electromagnetic wave absorption properties, and usually needs to be loaded with functional fillers to give it multifunctionality.
[0004] Two-dimensional layered materials exhibit unique thermal and electromagnetic properties due to their unique structure, rich surface, and huge surface area generated by their two-dimensional geometry, providing a way to create composite materials with customized multifunctional properties. Among them, the lateral size and aspect ratio of boron nitride (BN) nanosheets make their thermal conductivity as high as 400W / mK or more at room temperature. Graphene (RGO) nanosheets have attracted attention in the field of wave absorption due to their high thermal conductivity, large aspect ratio and high temperature stability. MXene nanosheets also show great potential in the field of wave absorption due to their rich surface functional groups, excellent conductivity and processability.
[0005] Research has found that high filler loading is often required to obtain high-performance silicone rubber elastomers, but at high filler loading, it is important to achieve effective dispersion of the filler in the silicone rubber matrix. At the nanoscale, two-dimensional layered materials tend to agglomerate due to their high surface energy. In addition, the compatibility between the filler and the silicone rubber matrix will also affect the performance of the composite material.
[0006] Direct ink writing (DIW) technology is a 3D printing technology that allows users to design and customize printed structures by stacking them layer by layer. It is widely used in the manufacture of elastomers due to its unique advantages such as low cost, high efficiency and rapid prototyping. However, 3D printing has high requirements on the rheological properties of printing inks. On the one hand, the printing inks must have the characteristics of shear thinning. On the other hand, the printing inks must be extruded through micron-sized needles while still ensuring the uniformity of the ink components and without clogging the needles. However, the lamellar structure of two-dimensional layered materials can cause them to stack and easily agglomerate, which not only significantly increases the viscosity of the printing inks and blocks the printing needles, but also affects the mechanical properties of silicone rubber.
[0007] Therefore, a new technology for preparing hydrophobic composite materials is needed to meet the application in 3D printing silicone rubber. Summary of the invention
[0008] The hydrophobic composite material provided by the present invention includes a two-dimensional layered material and silicon dioxide, and the silicon dioxide is distributed on the surface of the two-dimensional layered material and / or embedded and distributed between the sheets of the two-dimensional layered material. The hydrophobic composite material provided by the present invention is prepared by a one-step method of continuous spray drying, and the preparation process of the hydrophobic composite material is simple, the cycle is short, the versatility is strong, the raw material selection space is large, and the combination of the two-dimensional layered material and silicon dioxide can be achieved in one step, and the performance of the two-dimensional layered material itself can be guaranteed while also having the characteristics of good compatibility with silicone rubber. In addition, the present invention can realize the preparation of a spherical hydrophobic composite material in one step, and the viscosity of the 3D printing silicone rubber ink prepared by the hydrophobic composite material is low, and the printability of the hydrophobic composite material can be achieved. The hydrophobic composite material provided by the present invention can be used to prepare 3D printing silicone rubber, and the obtained 3D printing silicone rubber has thermal conductivity and / or electromagnetic wave absorption performance, and has good mechanical strength, and can be widely used in the fields of thermal management and electromagnetic wave absorption.
[0009] In the present invention, silicon dioxide, as a zero-dimensional material, can not only improve the interfacial compatibility with silicone rubber elastomers, but also be dispersed on the surface and / or interlayer of nanosheets, thereby achieving the effect of preventing the stacking of two-dimensional nanosheets. Therefore, by utilizing the excellent thermal conductivity and electromagnetic wave absorption properties of two-dimensional layered materials, combining them with silicon dioxide nanoparticles, it is possible to obtain the characteristics of good compatibility with silicone rubber while ensuring the performance of the two-dimensional layered materials themselves, providing ideas for preparing functional silicone rubber elastomers. In view of this, a hydrophobic composite material of the present application and a preparation method thereof and an application in 3D printing silicone rubber are proposed.
[0010] The object of the present invention is achieved through the following technical solutions:
[0011] <Hydrophobic composite material>
[0012] A hydrophobic composite material, comprising a two-dimensional layered material and silicon dioxide, wherein the silicon dioxide is distributed on the surface of the two-dimensional layered material and / or is embedded and distributed between the lamellae of the two-dimensional layered material; the hydrophobic composite material contains hydrophobic groups, wherein the hydrophobic groups are distributed on the surface of the two-dimensional layered material and / or between the lamellae of the two-dimensional layered material, and wherein the hydrophobic groups are distributed on the surface of the silicon dioxide.
[0013] According to an embodiment of the present invention, the hydrophobic group is at least one of a methyl group, an ethyl group and a vinyl group.
[0014] According to an embodiment of the present invention, the hydrophobic group is derived from a hydrophobic modifier, and the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane.
[0015] According to an embodiment of the present invention, the mass ratio of the two-dimensional layered material and the silica is 1:(0.1-4), such as 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3 or 1:4. The thermal conductivity and electromagnetic wave absorption performance of the hydrophobic composite material can be adjusted by adjusting the mass ratio of the two-dimensional layered material and the silica; wherein, when the mass ratio of the two-dimensional layered material and the silica is 1:(0.1-4), it is conducive to the mutual intercalation between the two-dimensional layered materials, and it can also ensure that the silica is uniformly dispersed on the surface and / or between the sheets of the two-dimensional layered material, avoiding the stacking of the two-dimensional layered material and the agglomeration of the silica, and it can ensure that the thermal conductivity and electromagnetic wave absorption performance of the obtained hydrophobic composite material are effectively improved.
[0016] According to an embodiment of the present invention, the two-dimensional layered material is selected from at least one of boron nitride (BN) modified by a hydrophobic modifier, graphene (RGO) modified by a hydrophobic modifier, and MXene modified by a hydrophobic modifier, wherein the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and dimethoxymethylphenylsilane.
[0017] According to an embodiment of the present invention, the chemical formula of the MXene is M n+1 C n T x , wherein n is 1, 2 or 3, M is at least one of Ti, Nb, Mo and V, and T is at least one of -OH, -F and -O; exemplarily, the MXene is selected from Ti3C2T x 、Ti2CT x 、Nb4C3T x 、V2CT x 、Mo2Ti2C3T x 、Nb2CT x and Mo2TiC2T x At least one of .
[0018] According to an embodiment of the present invention, the chemical formula of the MAX phase is M n+1 AX n , wherein n is 1, 2 or 3, M is at least one of Ti, Nb, Mo and V, A is Al, Sn, and X is C, N; exemplarily, the MAX phase includes at least one of Ti3AlC2, Ti3AlCN, Ti2AlC, Ti2AlN, V2AlC, Mo2TiAiC2, Nb2AlC, Nb2SnC and Ta2AlC. Exemplarily, the few-layer Ti3C2T x MXene is prepared by selectively etching the A atomic layer in the Ti3AlC2 MAX phase with HF (LiF-HCl system).
[0019] According to an embodiment of the present invention, the boron nitride (BN) is prepared by a method known in the art; and the graphene (RGO) is prepared by a method known in the art.
[0020] According to an embodiment of the present invention, the silica is at least one of fumed silica modified by a hydrophobic modifier, precipitated silica modified by a hydrophobic modifier and silica sol modified by a hydrophobic modifier; wherein the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane.
[0021] According to an embodiment of the present invention, the fumed silica is fumed silica prepared by a gas phase method known in the art; the precipitated silica is precipitated silica prepared by a precipitation method known in the art; and the silica sol is prepared by a method known in the art.
[0022] According to an embodiment of the present invention, the silicon dioxide and the two-dimensional layered material are connected by physical action and / or chemical bond interaction, and the physical action and / or chemical bond interaction is conducive to the close combination of silicon dioxide and the two-dimensional layered material. The two-dimensional layered materials are connected by physical action and / or chemical bond interaction, and the physical action and / or chemical bond interaction is conducive to the close combination between the two-dimensional layered materials.
[0023] According to an embodiment of the present invention, the hydrophobic composite material has a porous spherical structure.
[0024] According to an embodiment of the present invention, the average particle size of the hydrophobic composite material is 2-25 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm.
[0025] According to an embodiment of the present invention, the two-dimensional layered material and silica are hydrophobically modified using a hydrophobic modifier, which is beneficial to improving the dispersibility of the hydrophobic composite material formed by the two-dimensional layered material and silica in the silicone rubber matrix, so that the hydrophobic composite material and the silicone rubber have good compatibility, which is beneficial to preparing 3D printing silicone rubber ink for preparing silicone rubber, meeting the requirements of 3D printing; more importantly, it can ensure that the thermal conductivity and electromagnetic wave absorption performance of the hydrophobic composite material are effectively improved.
[0026] <Method for preparing hydrophobic composite material>
[0027] The present invention also provides a method for preparing the hydrophobic composite material, the method comprising the following steps:
[0028] (1) mixing a two-dimensional layered material, a hydrophobic modifier, a surfactant, silicon dioxide and a solvent, and subjecting the mixture to ultrasonic crushing and stirring to obtain a modified suspension;
[0029] (2) The modified suspension obtained in step (1) is passed into a continuous spray dryer for spray drying. Droplets of the modified suspension sprayed from the spray dryer are rapidly vaporized at high temperature, and then separated by a cyclone separator and collected in a collector to obtain the hydrophobic composite material.
[0030] According to an embodiment of the present invention, in step (1), the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane.
[0031] According to an embodiment of the present invention, in step (1), the solvent is selected from at least one of water, ethanol, propanol, isopropanol, butanol and methanol.
[0032] According to an embodiment of the present invention, in step (1), the two-dimensional layered material is selected from at least one of boron nitride (BN), graphene (RGO) and MXene.
[0033] According to an embodiment of the present invention, in step (1), the MXene is preferably a MXene suspension.
[0034] According to the embodiment of the present invention, in step (1), the MXene suspension is prepared by the following method: 1) weighing 1-3 g of LiF into a polytetrafluoroethylene beaker, slowly adding 10-60 ml of 9 mol / L-12 mol / L hydrochloric acid and stirring for 20-40 min at a speed of 400-800 rpm; 2) 1-3 g of LiF The MAX phase is slowly added to the above mixed solution, the reaction temperature is 35-45°C, and stirring is continued for 24-36h; 3) After the reaction is completed, the product is first washed with deionized water and / or ethanol and ultrasonically treated for 10-30min, then centrifuged at a speed of 3500-5000rpm for 10-15min, the supernatant is discarded, and the operation is repeated until the pH of the supernatant is ≥5; the precipitate is then mixed with deionized water and / or ethanol and ultrasonically treated for 10-30min, then centrifuged at a speed of 8000-10000rpm for 10-20min, and the supernatant is discarded; finally, the precipitate is mixed with deionized water and / or ethanol and ultrasonically treated for 10-30min, then centrifuged at a speed of 3500-5000rpm for 3-10min to obtain a MXene suspension.
[0035] According to an embodiment of the present invention, in step (1), the surfactant is selected from a dispersant, a defoamer and a binder. Exemplarily, the dispersant is selected from at least one of PEG400, OP-10, ammonium acetate, ammonium sulfate, polyether F127, PEG1000, PEG6000, PEG10000 and anionic dodecylbenzene sulfonic acid; the defoamer is selected from at least one of silicone, alcohol ketone, isopentanol, ethanol and diethylhexanol; the binder is selected from at least one of polyvinyl alcohol, hydroxycellulose, glycerol, PEG2000, polyacrylamide, glycerol, polyvinyl pyrrolidone K29-32 and polyacrylic acid.
[0036] According to an embodiment of the present invention, in step (1), the silicon dioxide is selected from at least one of fumed silicon dioxide, precipitated silicon dioxide and silica sol.
[0037] According to an embodiment of the present invention, in step (1), the mass of the surfactant accounts for 0.0001-6.05 wt % of the total mass of the modified suspension. Exemplarily, the mass of the binder accounts for 0.01wt%-3wt% of the total mass of the modified suspension, for example, 0.01wt%, 0.03wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 2wt% or 3wt%; the mass of the dispersant accounts for 0.01wt%-3wt% of the total mass of the modified suspension, for example, 0.01wt%, 0.03wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 2wt% or 3wt%; the mass of the defoamer accounts for 0.0001wt%-0.05wt% of the total mass of the modified suspension, for example, 0.0001wt%, 0.001wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt% or 0.05wt%.
[0038] According to an embodiment of the present invention, in step (1), the mass of the two-dimensional layered material accounts for 0.1wt%-15wt% of the total mass of the modified suspension, for example, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 7.5wt%, 10wt%, 12.5wt% or 15wt%.
[0039] According to an embodiment of the present invention, in step (1), the mass of the silicon dioxide accounts for 0.1wt%-15wt% of the total mass of the modified suspension, for example, 0.1wt%, 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 7.5wt%, 10wt%, 12.5wt% or 15wt%.
[0040] According to an embodiment of the present invention, in step (1), the mass ratio of the two-dimensional layered material to silicon dioxide in the modified suspension is 1:(0.1-4), for example, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3 or 1:4.
[0041] According to an embodiment of the present invention, in step (1), the total mass of the two-dimensional layered material and silicon dioxide accounts for 0.2wt%-30wt% of the total mass of the modified suspension, such as 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%.
[0042] According to an embodiment of the present invention, in step (1), the mass of the hydrophobic modifier accounts for 5wt%-40wt% of the total mass of the modified suspension, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or 40wt%.
[0043] According to an embodiment of the present invention, in step (1), the mass of the solvent accounts for 35wt%-90wt% of the total mass of the modified suspension, for example, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%.
[0044] According to an embodiment of the present invention, in step (1), the ultrasonic disruption is performed using an ultrasonic cell disruptor, and the stirring treatment is performed using a magnetic stirrer. Exemplarily, the power of the ultrasonic disruption is 300-600 W, and the ultrasonic disruption time is 2-10 hours; the rotation speed of the stirring treatment is 400-800 rpm, and the stirring treatment time is 1-4 hours.
[0045] According to an embodiment of the present invention, in step (2), the cyclone separator and collector are commonly used devices known in the art and used in conjunction with a spray dryer to achieve product separation and collection.
[0046] According to an embodiment of the present invention, in step (2), an inert gas is introduced into the continuous spray dryer, that is, the spray drying is carried out in the presence of an inert gas; the inert gas is, for example, nitrogen or argon.
[0047] According to an embodiment of the present invention, in step (2), the parameters of the spray drying include: the feed airflow of the modified suspension is 10-40 mm / min, for example, 10 mm / min, 15 mm / min, 20 mm / min, 25 mm / min, 30 mm / min, 35 mm / min or 40 mm / min; the inlet temperature of the spray dryer is 90-150°C (for example, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C), and the inlet temperature of the spray dryer is higher than the boiling point of the solvent; the outlet temperature of the spray dryer is 70-130°C (for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or 130°C).
[0048] According to an embodiment of the present invention, in step (2), the spray dryer is provided with an organic solvent recovery device.
[0049] According to an embodiment of the present invention, in step (2), the inner wall of the spray dryer is provided with a coating, and the provision of the coating can effectively prevent the hydrophobic composite material from remaining inside the spray dryer.
[0050] According to the embodiment of the present invention, in step (2), the dispersant in the modified suspension can promote the stable dispersion of the modified suspension; the binder in the modified suspension can increase the interaction force between the two-dimensional layered material with a nanosheet structure and the silicon dioxide with a nanoparticle structure, thereby ensuring the tightness of the hydrophobic composite material; the defoamer in the modified suspension can eliminate the bubbles in the modified suspension, thereby avoiding the problem of difficulty in balling due to excessive bubbles. In the spray drying process, when the modified suspension is sprayed into tiny spherical droplets inside the spray dryer, since the temperature at the inlet of the spray dryer is higher than the boiling point of the solvent, the two-dimensional layered material with a nanosheet structure and the silicon dioxide with a nanoparticle structure are rapidly curled and intercalated under the action of the surface tension of the solvent (specifically, the two-dimensional layered material with a nanosheet structure is intercalated with each other, and the silicon dioxide with a nanoparticle structure is dispersed on the surface and / or between the two-dimensional layered material with a nanosheet structure), thereby continuously preparing a hydrophobic composite material with a porous spherical structure with high overall structural stability through a one-step method.
[0051] According to the embodiment of the present invention, the preparation method of the hydrophobic composite material is simple, economical and green, and can realize convenient and mass production of the hydrophobic composite material.
[0052] <Hydrophobic composite material>
[0053] The present invention also provides a hydrophobic composite material prepared by the method.
[0054] <Application of hydrophobic composite materials>
[0055] The present invention also provides the use of the hydrophobic composite material, which is used in the field of 3D printing silicone rubber.
[0056] According to an embodiment of the present invention, the 3D printing is direct ink writing 3D printing.
[0057] <3D printing silicone rubber ink>
[0058] The present invention also provides a 3D printing silicone rubber ink, which comprises the above-mentioned hydrophobic composite material, liquid silicone rubber and a curing agent.
[0059] According to an embodiment of the present invention, the 3D printing silicone rubber ink comprises the following components in percentage by mass:
[0060] Hydrophobic composite material 5-35wt%;
[0061] Liquid silicone rubber 55-90wt%;
[0062] Curing agent 5-10wt%.
[0063] According to an embodiment of the present invention, the mass of the curing agent accounts for 5-10wt% of the total mass of the 3D printing silicone rubber ink, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%; the mass of the hydrophobic composite material accounts for 5-35wt% of the total mass of the 3D printing silicone rubber ink, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or 35wt%; the mass of the liquid silicone rubber accounts for 55-90wt% of the total mass of the 3D printing silicone rubber ink, for example, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%.
[0064] According to an embodiment of the present invention, the viscosity of the liquid silicone rubber is 10-10 5 Pa·s.
[0065] According to an embodiment of the present invention, the liquid silicone rubber can be prepared by a method known in the art, or purchased through commercial channels.
[0066] According to an embodiment of the present invention, the curing agent is purchased from a commercial source and is a curing agent used for curing liquid silicone rubber known in the art. Exemplarily, the curing agent is selected from at least one of a platinum catalyst, an organic tin catalyst or a titanate catalyst.
[0067] <Method for preparing 3D printing silicone rubber ink>
[0068] The present invention also provides a method for preparing the above 3D printing silicone rubber ink, the method comprising the following steps:
[0069] The hydrophobic composite material, liquid silicone rubber and a curing agent are mixed and degassed to prepare 3D printing silicone rubber ink.
[0070] According to an embodiment of the present invention, the mixing is performed under stirring conditions, the stirring speed is 1000-2000 rpm, and the stirring time is 10-30 min. Exemplarily, the mixing is performed in a planetary mixer.
[0071] According to an embodiment of the present invention, the degassing is centrifugal degassing, the rotation speed of the centrifugal degassing is 1000-2000 rpm, the time of the centrifugal degassing is 1-10 min, and the number of centrifugal degassing is 1-3 times.
[0072] <Application of 3D printing silicone rubber ink>
[0073] The present invention also provides the use of the above 3D printing silicone rubber ink, which is used in the field of 3D printing silicone rubber.
[0074] <3D Printing Silicone Rubber>
[0075] The present invention also provides a 3D printing silicone rubber, wherein the 3D printing silicone rubber is prepared by the above-mentioned 3D printing silicone rubber ink.
[0076] According to an embodiment of the present invention, the 3D printing silicone rubber is prepared by 3D printing the above-mentioned 3D printing silicone rubber ink.
[0077] According to an embodiment of the present invention, the 3D printing is direct ink writing 3D printing.
[0078] According to an embodiment of the present invention, the parameters of the 3D printing include: an extrusion pressure of 0.4-4kgf, an extrusion speed of 0.002-0.01g / s, a printing layer height of 0.2-0.8mm, and a platform spacing of 0.2-0.8mm.
[0079] The present invention also provides a 3D printing silicone rubber, wherein the raw materials for preparing the 3D printing silicone rubber include the above-mentioned 3D printing silicone rubber ink.
[0080] <Method for preparing 3D printing silicone rubber>
[0081] The present invention also provides a method for preparing 3D printing silicone rubber, the method comprising the following steps:
[0082] (a) Transferring 3D printing silicone rubber ink to the printing device, designing and slicing the printing model, setting printing parameters, adjusting the printing platform, and printing the desired pattern or structure;
[0083] (b) heat treating the pattern or structure printed in step (a) to obtain 3D printed silicone rubber.
[0084] According to an embodiment of the present invention, in step (a), the printing parameters include: extrusion pressure of 0.4-4kgf, extrusion speed of 0.002-0.01g / s, printing layer height of 0.2-0.8mm, and platform spacing of 0.2-0.8mm.
[0085] According to an embodiment of the present invention, in step (b), a gradient heating method is used for heat treatment, the temperature of the first heating stage is 80-100°C, the time of the first heating stage is 20-60min, and the purpose of the first heating stage is to achieve degassing of the curing system and prepolymerization of the silicone rubber; the temperature of the second heating stage is 120-150°C, the time of the second heating stage is 10-30min, and the purpose of the second heating stage is to achieve further crosslinking of the silicone rubber polymer.
[0086] <3D Printing Silicone Rubber>
[0087] The present invention also provides a 3D printing silicone rubber, which is prepared by the above method.
[0088] <Applications of 3D Printing Silicone Rubber>
[0089] The present invention also provides the use of the above 3D printing silicone rubber, which is used in the fields of electromagnetic wave absorption and thermal management.
[0090] According to an embodiment of the present invention, a component for electromagnetic wave absorption and heat management having excellent flexibility is prepared.
[0091] Beneficial effects of the present invention:
[0092] The present invention adopts continuous spray spheroidization technology, obtains modified suspension by compounding silicon dioxide and two-dimensional layered materials and selecting hydrophobic modifiers and solvents; then uses a continuous spray dryer to spray the modified suspension into tiny spherical droplets; because the temperature at the inlet of the spray dryer is higher than the boiling point of the solvent, the two-dimensional layered materials with nanosheet structures and the silicon dioxide with nanoparticle structures are rapidly curled and intercalated under the action of the surface tension of the solvent (specifically, the two-dimensional layered materials with nanosheet structures are intercalated with each other, and the silicon dioxide with nanoparticle structures is dispersed on the surface and / or between the layers of the two-dimensional layered materials with nanosheet structures); through the interaction between the silicon dioxide and the two-dimensional layered materials, the stacking of the two-dimensional layered materials and the agglomeration of the silicon dioxide can be effectively avoided, and the one-step preparation of the hydrophobic composite material is achieved.
[0093] The continuous spray spheronization technology of the present invention can directly dry the hydrophobic composite material to directly obtain a hydrophobic composite material with a porous spherical structure, giving the hydrophobic composite material and silicone rubber good compatibility and low thickening characteristics. Compared with a single hydrophobic two-dimensional layered material or a single hydrophobic silica, the introduction of the hydrophobic composite material of the present invention is more conducive to improving the performance of silicone rubber.
[0094] The presence of structures such as porous skeleton, interfacial effect between two-dimensional layered material sheets, heterojunction of two-dimensional layered material and silicon dioxide in the hydrophobic composite material of the present invention is conducive to the formation of multiple scattering losses in the hydrophobic composite material in the silicone rubber, promotes electromagnetic wave dissipation, improves impedance matching, and is conducive to enhancing microwave absorption. When the silicone rubber containing the hydrophobic composite material is used in the field of electromagnetic wave absorption and thermal management, more outstanding effects will be achieved. The hydrophobic composite material contains hydrophobic groups, and the intermolecular interaction force of the hydrophobic composite material can provide more action sites between the filler and the matrix, which is conducive to improving the mechanical properties of 3D printed silicone rubber; at the same time, the hydrophobic composite material also retains the shape and characteristics of the two-dimensional layered material itself, so that it has good thermal conductivity and electromagnetic wave absorption performance. The 3D printed silicone rubber prepared using the hydrophobic composite material can have good electromagnetic wave absorption performance, thermal conductivity and mechanical properties. With the help of direct ink writing 3D printing technology, customized manufacturing of complex structures can be realized, so that it is suitable for various application scenarios such as thermal management and electromagnetic wave absorption elastomers, and has a wide range of application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 A scanning electron microscope image of the hydrophobic MXene@RGO@SiO2 functional microspheres of Example 3 is shown.
[0096] Figure 2 The scanning electron microscope image of the hydrophobic BN@SiO2 functional microspheres of Example 4 is shown.
[0097] Figure 3 The scanning electron microscope image of the hydrophobic RGO@BN@SiO2 functional microspheres of Example 5 is shown.
[0098] Figure 4 Optical images showing the 3D printing process of the 3D printed silicone rubber of Example 2.
[0099] Figure 5 The electromagnetic wave absorption performance of the 3D printed silicone rubber of Example 2 is shown. DETAILED DESCRIPTION
[0100] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0101] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0102] Example 1
[0103] (1) Etching Ti3Al2C using LiF-HCl system x Preparation of Ti3C2T from MAX phase x MXene suspension:
[0104] 1g of LiF was added to 30ml of 10mol / L hydrochloric acid solution and stirred for 20min at a speed of 500rpm; then 1g of MAX Ti3AlC2 was slowly added to the above mixed solution, the reaction temperature was 35℃, and stirring was continued for 30h; after the reaction, the product was first washed with ethanol and ultrasonically treated for 20min, then centrifuged at a speed of 3500rpm for 10min, the supernatant was discarded, and the operation was repeated until the pH of the supernatant was ≥5; the precipitate was then mixed with deionized water and ethanol (volume ratio 1:1) and ultrasonically treated for 10min, then centrifuged at a speed of 8000rpm for 10min, and the supernatant was discarded; finally, the precipitate was mixed with deionized water and ethanol (volume ratio 1:1) and ultrasonically treated for 10min, then centrifuged at a speed of 5000rpm for 3min to obtain the exfoliated Ti3C2T x MXene suspension.
[0105] (2) 0.5wt% of the total mass of the modified suspension is mixed with a two-dimensional layered material, 39.58wt% of the modifier, 0.5wt% of fumed silica, 0.02wt% of polyvinyl alcohol, 0.02wt% of PEG1000, 0.001wt% of silicone, and a solvent, and the mixture is ultrasonically crushed for 4 hours and then stirred for 3 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of graphene and MXene in a mass ratio of 1:4; the modifier is composed of diethylsiloxane; and the solvent is composed of ethanol and water (volume ratio 1:1).
[0106] (3) The modified suspension was passed into a continuous spray dryer, and the droplets of the modified suspension were rapidly vaporized under an inert gas with an inlet temperature of 130°C, an outlet temperature of 100°C, and a feed gas flow of 25 mm / min. After separation in a cyclone separator, hydrophobic MXene@RGO@SiO2 functional microspheres were obtained in a collector.
[0107] (4) The average particle size of the hydrophobic MXene@RGO@SiO2 functional microspheres obtained in this embodiment is ≤10 μm, and they are printable.
[0108] (5) The hydrophobic MXene@RGO@SiO2 functional microspheres, liquid silicone rubber and curing agent were mixed and centrifuged for degassing at a centrifugal speed of 1000 rpm for 10 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of MXene@RGO@SiO2 functional microspheres was 30 wt%, the mass percentage of liquid silicone rubber was 60 wt%, and the mass percentage of curing agent was 10 wt%.
[0109] (6) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.6 mm needle, setting the extrusion parameters to an extrusion pressure of 2.9 kgf and an extrusion speed of 0.01 g / s, wherein the platform spacing is 0.5 mm, the layer height is 0.4 mm, and the printing platform is adjusted to print the desired pattern or structure;
[0110] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 30 min, the second heating temperature was 120°C, and the second heating time was 20 min.
[0111] (7) The minimum reflection loss RL of the 3D printed silicone rubber at a thickness of 2 mm min It is -31.7dB, and the effective absorption bandwidth is 3.2GHz; the thermal conductivity of the printed 3D printed silicone rubber is 0.4W / (mK).
[0112] Example 2
[0113] (1) Etching Ti3Al2C using LiF-HCl system x Preparation of Ti3C2T from MAX phase x MXene suspension:
[0114] 2g of LiF was added to 40ml of 12mol / L hydrochloric acid solution and stirred for 30min at a speed of 700rpm. Then, 2g of MAX Ti3AlC2 was slowly added to the mixed solution. The reaction temperature was 35°C and the stirring was continued for 28h. After the reaction, the product was washed with ethanol and ultrasonically treated for 10min, then centrifuged at a speed of 4000rpm for 10min, and the supernatant was discarded. The operation was repeated until the pH of the supernatant was ≥5. The precipitate was mixed with ethanol and ultrasonically treated for 10min, then centrifuged at a speed of 10000rpm for 15min, and the supernatant was discarded. Finally, the precipitate was mixed with ethanol and ultrasonically treated for 10min, and then centrifuged at a speed of 3500rpm for 3min to obtain the exfoliated Ti3C2T x MXene suspension.
[0115] (2) A two-dimensional layered material accounting for 1 wt% of the modified suspension, a modifier of 29.54 wt%, a silica sol of 0.5 wt%, polyvinyl pyrrolidone K30 of 0.02 wt%, OP-10 of 0.002 wt%, and a solvent are mixed, and the mixture is ultrasonically crushed for 6 hours and stirred for 3 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of graphene and MXene in a mass ratio of 1:2; the modifier is composed of hexamethyldisiloxane and dimethyldiethoxysilane (volume ratio of 6:4); and the solvent is composed of ethanol.
[0116] (3) The modified suspension was passed into a continuous spray dryer, and the droplets of the modified suspension were rapidly vaporized under an inert gas with an inlet temperature of 120°C, an outlet temperature of 90°C, and a feed gas flow of 40 mm / min. After separation in a cyclone separator, hydrophobic MXene@RGO@SiO2 functional microspheres were obtained in a collector.
[0117] (4) The average particle size of the hydrophobic MXene@RGO@SiO2 functional microspheres obtained in this embodiment is ≤20 μm, and they are printable.
[0118] (5) The hydrophobic MXene@RGO@SiO2 functional microspheres, liquid silicone rubber and curing agent were mixed and centrifuged for degassing at a centrifugal speed of 2000 rpm for 5 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of MXene@RGO@SiO2 functional microspheres was 25wt%, the mass percentage of liquid silicone rubber was 65wt%, and the mass percentage of curing agent was 10wt%.
[0119] (6) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.4 mm needle, setting the extrusion parameters to an extrusion pressure of 3.5 kgf and an extrusion speed of 0.003 g / s, wherein the platform spacing is 0.4 mm, the layer height is 0.3 mm, and the printing platform is adjusted to print the desired pattern or structure;
[0120] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 30 min, the second heating temperature was 150°C, and the second heating time was 30 min.
[0121] (7) The minimum reflection loss RL of the 3D printed silicone rubber at a thickness of 2 mm min It is -34dB, and the effective absorption bandwidth is 4GHz; the thermal conductivity of the printed 3D printed silicone rubber is 0.5W / (mK). Figure 2 This is an optical image of the 3D printing process of the 3D printed silicone rubber of Example 2. Figure 5 The electromagnetic wave absorption performance of 3D printed silicone rubber.
[0122] Example 3
[0123] (1) Etching Ti3Al2C using LiF-HCl system x Preparation of Ti3C2T from MAX phase x MXene suspension:
[0124] 1g of LiF was added to 30ml of 9mol / L hydrochloric acid solution and stirred for 30min at a speed of 600rpm. Then, 1g of MAX Ti3AlC2 was slowly added to the mixed solution, the reaction temperature was 40℃, and stirring was continued for 36h. After the reaction, the product was washed with water and ultrasonically treated for 20min, then centrifuged at a speed of 3500rpm for 10min, the supernatant was discarded, and the operation was repeated until the pH of the supernatant was ≥5. The precipitate was then mixed with ethanol and deionized water (volume ratio 3:1) and ultrasonically treated for 10min, then centrifuged at a speed of 10000rpm for 15min, and the supernatant was discarded. Finally, the precipitate was mixed with ethanol and deionized water (volume ratio 3:1) and ultrasonically treated for 10min, then centrifuged at a speed of 4000rpm for 5min to obtain the exfoliated Ti3C2T x MXene suspension.
[0125] (2) 1.5 wt% of the modified suspension is composed of a two-dimensional layered material, 38.96 wt% of a modifier, 1 wt% of fumed silica, 0.05 wt% of hydroxycellulose, 0.05 wt% of dodecylbenzenesulfonic acid 1000, 0.002 wt% of isoamyl alcohol, and a solvent, and the mixture is ultrasonically crushed for 10 hours and then stirred for 2 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of graphene and MXene in a mass ratio of 2:1; the modifier is composed of 1,3-diphenyl-1,1,3,3-tetramethyldisilazane; and the solvent is composed of propanol and water (volume ratio 3:1).
[0126] (3) The modified suspension was passed into a continuous spray dryer, and the droplets of the modified suspension were rapidly vaporized under an inert gas with an inlet temperature of 130°C, an outlet temperature of 100°C, and a feed gas flow of 40 mm / min. After separation in a cyclone separator, hydrophobic MXene@RGO@SiO2 functional microspheres were obtained in a collector.
[0127] (4) The average particle size of the hydrophobic MXene@RGO@SiO2 functional microspheres obtained in this embodiment is ≤10 μm, and they are printable.
[0128] (5) The hydrophobic MXene@RGO@SiO2 functional microspheres, liquid silicone rubber and curing agent were mixed and centrifuged for degassing at a centrifugal speed of 2000 rpm for 8 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of MXene@RGO@SiO2 functional microspheres was 20 wt%, the mass percentage of liquid silicone rubber was 70 wt%, and the mass percentage of curing agent was 10 wt%.
[0129] (6) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.4 mm needle, setting the extrusion parameters to an extrusion pressure of 3.6 kgf and an extrusion speed of 0.003 g / s, wherein the platform spacing is 0.4 mm, the layer height is 0.3 mm, and adjusting the printing platform to print the desired pattern or structure;
[0130] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 30 min, the second heating temperature was 150°C, and the second heating time was 30 min.
[0131] (7) The minimum reflection loss RL of the 3D printed silicone rubber at a thickness of 2 mm min The effective absorption bandwidth is -38dB and 4.1GHz. The thermal conductivity of the 3D printed silicone rubber is 0.6W / (mK). Figure 1 This is a scanning electron microscope image of the hydrophobic MXene@RGO@SiO2 functional microspheres of Example 3.
[0132] Example 4
[0133] (1) A two-dimensional layered material accounting for 3 wt% of the modified suspension, a modifier of 28.79 wt%, precipitated silica of 1 wt%, 0.02 wt% of propylene glycol, 0.02 wt% of polyether F127, 0.002 wt% of alcohol ketone, and a solvent are mixed, and the mixture is ultrasonically crushed for 8 hours and then stirred for 3 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of boron nitride; the modifier is composed of dimethyldimethoxysilane and tetramethyldivinyldisilazane (volume ratio 1:1); and the solvent is composed of ethanol.
[0134] (2) The modified suspension is passed into a continuous spray dryer, and the droplets of the modified suspension are rapidly vaporized under an inert gas with an inlet temperature of 120°C, an outlet temperature of 90°C, and a feed gas flow of 20 mm / min. After separation in a cyclone separator, hydrophobic BN@SiO2 functional microspheres are obtained in a collector.
[0135] (3) The average particle size of the hydrophobic BN@SiO2 functional microspheres obtained in this embodiment is ≤15 μm and is printable.
[0136] (4) The hydrophobic BN@SiO2 functional microspheres, liquid silicone rubber and curing agent are mixed and centrifuged for degassing at a centrifugal speed of 1000 rpm for 5 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of BN@SiO2 functional microspheres is 35wt%, the mass percentage of liquid silicone rubber is 57wt%, and the mass percentage of curing agent is 8wt%.
[0137] (5) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.4 mm needle, setting the extrusion parameters to an extrusion pressure of 3.1 kgf and an extrusion speed of 0.004 g / s, wherein the platform spacing is 0.4 mm, the layer height is 0.3 mm, and adjusting the printing platform to print the desired pattern or structure;
[0138] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C for 30 min, and the second heating temperature was 120°C for 30 min.
[0139] (6) The thermal conductivity of the 3D printed silicone rubber is 0.8 W / (mK). Figure 2 This is a scanning electron microscope image of the hydrophobic BN@SiO2 functional microspheres of Example 4.
[0140] Example 5
[0141] (1) A two-dimensional layered material accounting for 2 wt% of the modified suspension, a modifier of 38.57 wt%, a fumed silica of 1.5 wt%, a polyvinyl pyrrolidone K29 of 0.05 wt%, a PEG1000 of 0.02 wt%, an ethanol of 0.001 wt%, and a solvent are mixed, and the mixture is ultrasonically crushed for 4 hours and then stirred for 4 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of graphene and boron nitride in a mass ratio of 1:1; the modifier is composed of dimethyldimethoxysilane; and the solvent is composed of ethanol.
[0142] (2) The modified suspension was passed into a continuous spray dryer, and the droplets of the modified suspension were rapidly vaporized under an inert gas with an inlet temperature of 120°C, an outlet temperature of 90°C, and a feed gas flow of 30 mm / min. After separation in a cyclone separator, hydrophobic BN@RGO@SiO2 functional microspheres were obtained in a collector.
[0143] (3) The average particle size of the hydrophobic BN@RGO@SiO2 functional microspheres obtained in this embodiment is ≤25 μm, and they are printable.
[0144] (4) The hydrophobic BN@RGO@SiO2 functional microspheres, liquid silicone rubber and curing agent were mixed and centrifuged for degassing at a centrifugal speed of 1000 rpm for 3 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of BN@RGO@SiO2 functional microspheres was 20wt%, the mass percentage of liquid silicone rubber was 72wt%, and the mass percentage of curing agent was 8wt%.
[0145] (5) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.6 mm needle, setting the extrusion parameters to an extrusion pressure of 2.8 kgf and an extrusion speed of 0.004 g / s, wherein the platform spacing is 0.6 mm, the layer height is 0.5 mm, adjusting the printing platform, and printing the desired pattern or structure;
[0146] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 20 min, the second heating temperature was 120°C, and the second heating time was 20 min.
[0147] (6) The thermal conductivity of the 3D printed silicone rubber is 0.65 W / (mK). Figure 3 This is a scanning electron microscope image of the hydrophobic RGO@BN@SiO2 functional microspheres of Example 5.
[0148] Example 6
[0149] (1) A two-dimensional layered material accounting for 1 wt% of the modified suspension, a modifier of 29.39 wt%, precipitated silica of 1 wt%, 0.02 wt% of propylene glycol, 0.02 wt% of polyether F127, 0.002 wt% of alcohol ketone, and a solvent are mixed, and the mixture is ultrasonically crushed for 4 hours and then stirred for 3 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of graphene; the modifier is composed of dimethyldimethoxysilane and tetramethyldivinyldisilazane (volume ratio 1:1); and the solvent is composed of ethanol.
[0150] (2) The modified suspension is passed into a continuous spray dryer, and the modified suspension droplets are rapidly vaporized under an inert gas with an inlet temperature of 120°C, an outlet temperature of 90°C, and a feed gas flow of 30 mm / min. After separation in a cyclone separator, hydrophobic RGO@SiO2 functional microspheres are obtained in a collector.
[0151] (3) The average particle size of the hydrophobic RGO@SiO2 functional microspheres obtained in this embodiment is ≤15 μm, and they are printable.
[0152] (4) The hydrophobic RGO@SiO2 functional microspheres, liquid silicone rubber and curing agent are mixed, and centrifuged for degassing at a centrifugal speed of 1000 rpm for 5 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of RGO@SiO2 functional microspheres is 15wt%, the mass percentage of liquid silicone rubber is 77wt%, and the mass percentage of curing agent is 8wt%.
[0153] (5) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.4 mm needle, setting the extrusion parameters to an extrusion pressure of 3.6 kgf and an extrusion speed of 0.004 g / s, wherein the platform spacing is 0.4 mm, the layer height is 0.3 mm, and adjusting the printing platform to print the desired pattern or structure;
[0154] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 30 min, the second heating temperature was 120°C, and the second heating time was 30 min.
[0155] (6) The minimum reflection loss RL of the 3D printed silicone rubber at a thickness of 2 mm min The effective absorption bandwidth is -18dB and 2.1GHz. The thermal conductivity of the 3D printed silicone rubber is 0.45W / (mK).
[0156] Example 7
[0157] (1) Etching Ti3Al2C using LiF-HCl system x Preparation of Ti3C2T from MAX phase x MXene suspension:
[0158] 2g of LiF was added to 40ml of 12mol / L hydrochloric acid solution and stirred for 30min at a speed of 700rpm. Then, 2g of MAX Ti3AlC2 was slowly added to the mixed solution. The reaction temperature was 35°C and the stirring was continued for 28h. After the reaction, the product was washed with ethanol and ultrasonically treated for 10min, then centrifuged at a speed of 4000rpm for 10min, and the supernatant was discarded. The operation was repeated until the pH of the supernatant was ≥5. The precipitate was mixed with ethanol and ultrasonically treated for 10min, then centrifuged at a speed of 10000rpm for 15min, and the supernatant was discarded. Finally, the precipitate was mixed with ethanol and ultrasonically treated for 10min, and then centrifuged at a speed of 3500rpm for 3min to obtain the exfoliated Ti3C2T x MXene suspension.
[0159] (2) A two-dimensional layered material accounting for 1 wt% of the modified suspension, a modifier of 29.39 wt%, precipitated silica of 1 wt%, 0.02 wt% of propylene glycol, 0.02 wt% of polyether F127, 0.002 wt% of alcohol ketone, and a solvent are mixed, and the mixture is ultrasonically crushed for 4 hours and then stirred for 3 hours to obtain a uniformly dispersed modified suspension. The two-dimensional layered material is composed of MXene; the modifier is composed of dimethyldimethoxysilane and tetramethyldivinyldisilazane (volume ratio 1:1); and the solvent is composed of ethanol.
[0160] (3) The modified suspension is passed into a continuous spray dryer, and the droplets of the modified suspension are rapidly vaporized under an inert gas with an inlet temperature of 120°C, an outlet temperature of 90°C, and a feed gas flow of 20 mm / min. After separation in a cyclone separator, hydrophobic MXene@SiO2 functional microspheres are obtained in a collector.
[0161] (4) The average particle size of the hydrophobic MXene@SiO2 functional microspheres obtained in this embodiment is ≤10 μm, and they are printable.
[0162] (5) The hydrophobic MXene@SiO2 functional microspheres, liquid silicone rubber and curing agent are mixed and centrifuged for degassing at a centrifugal speed of 1000 rpm for 5 min to obtain 3D printing silicone rubber ink, wherein the mass percentage of MXene@SiO2 functional microspheres is 30 wt%, the mass percentage of liquid silicone rubber is 62 wt%, and the mass percentage of curing agent is 8 wt%.
[0163] (6) Transferring the 3D printing silicone rubber ink after centrifugal degassing to the loading tube used for printing, designing the printing model and slicing it, using a 0.4 mm needle, setting the extrusion parameters to an extrusion pressure of 2.6 kgf and an extrusion speed of 0.004 g / s, wherein the platform spacing is 0.4 mm, the layer height is 0.3 mm, and the printing platform is adjusted to print the desired pattern or structure;
[0164] The printed samples were heated and cured by a gradient heating method, wherein the first heating temperature was 80°C, the first heating time was 30 min, the second heating temperature was 120°C, and the second heating time was 30 min.
[0165] (7) The minimum reflection loss RL of the 3D printed silicone rubber at a thickness of 2 mm min It is -24dB and the effective absorption bandwidth is 1.2GHz.
[0166] Comparative Example 1
[0167] The other operations were the same as those in Example 2, except that no silica sol was added to the modified suspension, and hydrophobic MXene@RGO functional microspheres with an average particle size of ≤20 μm were prepared.
[0168] The hydrophobic MXene@RGO functional microspheres prepared above are used to replace the hydrophobic MXene@RGO@SiO2 functional microspheres in Example 2 for 3D printing. The printed 3D printed silicone rubber has a minimum reflection loss RL at 2 mm. min It is -21.6dB and the effective absorption bandwidth is 1.05GHz.
[0169] It can be seen from the performance test results of Example 2 and Comparative Example 1 that the functional microspheres of Comparative Example 1 do not contain silicon dioxide, which causes the two-dimensional layered materials in the obtained functional microspheres to stack and affect the electromagnetic absorption performance of the 3D printed silicone rubber finally prepared.
[0170] Comparative Example 2
[0171] The other operations were the same as those in Example 2, except that no modifier was added to the modified suspension, and MXene@RGO@SiO2 functional microspheres with an average particle size of ≤20 μm were prepared.
[0172] The hydrophobic MXene@RGO@SiO2 functional microspheres in Example 2 were replaced by the MXene@RGO@SiO2 functional microspheres prepared as above for 3D printing. The 3D printed silicone rubber obtained by 3D printing had a minimum reflection loss RL at 2 mm. min It is -18.4dB and the effective absorption bandwidth is 1.3GHz.
[0173] It can be seen from the performance test results of Example 2 and Comparative Example 2 that the functional microspheres of Comparative Example 2 have not been hydrophobically modified, which results in poor interface compatibility between the obtained functional microspheres and the silicone rubber, and poor dispersion of the functional microspheres in the silicone rubber matrix, which affects the electromagnetic absorption performance of the 3D printed silicone rubber finally prepared.
[0174] Comparative Example 3
[0175] (1) Liquid silicone rubber and a curing agent are mixed and centrifuged for degassing at a centrifugal speed of 2000 rpm for 5 minutes to obtain a 3D printing silicone rubber ink, wherein the mass percentage of the liquid silicone rubber is 90 wt % and the mass percentage of the curing agent is 10 wt %.
[0176] (2) The 3D printing silicone rubber ink after centrifugal degassing was transferred to the loading tube used for printing, the printing model was designed and sliced, a 0.4 mm needle was used, and the extrusion parameters were set to an extrusion pressure of 1.5 kgf and an extrusion speed of 0.003 g / s. The platform spacing was 0.4 mm, the layer height was 0.3 mm, and the printing platform was adjusted. The printed filament collapsed, making it difficult to carry out structural design.
[0177] It can be seen from the printing conditions of Example 2 and Comparative Example 3 that no filler is added in Comparative Example 3, which makes the ink unable to meet the shear thinning behavior and shaping ability required for printing, resulting in failure to perform printing.
[0178] Comparative Example 4
[0179] The other operations were the same as those in Example 4, except that no two-dimensional layered material was added to the modified suspension, and hydrophobic SiO2 functional microspheres with an average particle size of ≤10 μm were prepared.
[0180] The hydrophobic SiO2 functional microspheres prepared as above were used to replace the hydrophobic BN@SiO2 functional microspheres in Example 4 for 3D printing, and the 3D printed silicone rubber obtained had almost no thermal conductivity.
[0181] It can be seen from the performance test results of Example 4 and Comparative Example 4 that the functional microspheres of Comparative Example 4 do not contain two-dimensional layered materials, which causes agglomeration of silica in the obtained functional microspheres, affecting the performance of the 3D printing silicone rubber finally prepared.
[0182] Comparative Example 5
[0183] The other operations are the same as those in Example 4, except that the hydrophobic boron nitride and hydrophobic silica are not subjected to spherical treatment, but are directly mixed into the silicone rubber.
[0184] The hydrophobic boron nitride, hydrophobic silicon dioxide, liquid silicone rubber and curing agent were mixed, and centrifuged for degassing at a centrifugal speed of 1000 rpm for 5 minutes to obtain a 3D printing silicone rubber ink, wherein the mass percentage of hydrophobic boron nitride was 15wt%, the mass percentage of hydrophobic silicon dioxide was 5wt%, the mass percentage of liquid silicone rubber was 72wt%, and the mass percentage of curing agent was 8wt%.
[0185] The thermal conductivity of the 3D printed silicone rubber printed according to the printing method of Example 4 is 0.4 W / (mK).
[0186] It can be seen from the performance test results of Example 4 and Comparative Example 5 that when boron nitride and silicon dioxide are not subjected to spherical treatment but are directly added to the silicone rubber system, the proportion of fillers in the obtained silicone rubber is significantly reduced, and the interface compatibility between the filler and the silicone rubber is deteriorated, which affects the thermal conductivity of the 3D printing silicone rubber finally prepared. In the scheme of Example 4, not only can more fillers be added to the silicone rubber system, but also the interface compatibility between the filler and the silicone rubber can be ensured, thereby improving the performance of the 3D printing silicone rubber finally prepared.
[0187] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hydrophobic composite material, comprising a two-dimensional layered material and silicon dioxide, wherein the silicon dioxide is distributed on the surface of the two-dimensional layered material and / or is embedded and distributed between the lamellae of the two-dimensional layered material; the hydrophobic composite material contains hydrophobic groups, wherein the hydrophobic groups are distributed on the surface of the two-dimensional layered material and / or between the lamellae of the two-dimensional layered material, and wherein the hydrophobic groups are distributed on the surface of the silicon dioxide.
2. The hydrophobic composite material according to claim 1, wherein: The hydrophobic group is at least one of a methyl group, an ethyl group and a vinyl group. Preferably, the hydrophobic group is derived from a hydrophobic modifier, and the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane. Preferably, the mass ratio of the two-dimensional layered material to the silicon dioxide is 1:(0.1-4). Preferably, the two-dimensional layered material is selected from at least one of boron nitride (BN) modified by a hydrophobic modifier, graphene (RGO) modified by a hydrophobic modifier and MXene modified by a hydrophobic modifier, wherein the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane. Preferably, the silica is at least one of fumed silica modified by a hydrophobic modifier, precipitated silica modified by a hydrophobic modifier and silica sol modified by a hydrophobic modifier; wherein the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane. Preferably, the hydrophobic composite material has a porous spherical structure. Preferably, the average particle size of the hydrophobic composite material is 2-25 μm.
3. A method for preparing the hydrophobic composite material according to claim 1 or 2, comprising the following steps: (1) mixing a two-dimensional layered material, a hydrophobic modifier, a surfactant, silicon dioxide and a solvent, and subjecting the mixture to ultrasonic crushing and stirring to obtain a modified suspension; (2) The modified suspension obtained in step (1) is passed into a continuous spray dryer for spray drying. Droplets of the modified suspension sprayed from the spray dryer are rapidly vaporized at high temperature, and then separated by a cyclone separator and collected in a collector to obtain the hydrophobic composite material.
4. The method according to claim 3, wherein: In step (1), the hydrophobic modifier is selected from at least one of diethylsiloxane, dimethyldimethoxysilane, dimethyldiethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, hexamethyldisiloxane, hexamethyldisilazane, tetramethyldivinyldisiloxane, tetramethyldivinyldisilazane, 1,3-diphenyl-1,1,3,3-tetramethyldisilazane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dimethoxymethylphenylsilane. Preferably, in step (1), the solvent is selected from at least one of water, ethanol, propanol, isopropanol, butanol and methanol. Preferably, in step (1), the two-dimensional layered material is selected from at least one of boron nitride (BN), graphene (RGO) and MXene. Preferably, in step (1), the surfactant is selected from a dispersant, a defoaming agent and a binder. Preferably, in step (1), the silicon dioxide is selected from at least one of fumed silicon dioxide, precipitated silicon dioxide and silica sol. Preferably, in step (1), the mass of the surfactant accounts for 0.0001-6.05wt% of the total mass of the modified suspension. Exemplarily, the mass of the binder accounts for 0.01wt%-3wt% of the total mass of the modified suspension; the mass of the dispersant accounts for 0.01wt%-3wt% of the total mass of the modified suspension; the mass of the defoamer accounts for 0.0001wt%-0.05wt% of the total mass of the modified suspension. Preferably, in step (1), the mass of the two-dimensional layered material accounts for 0.1 wt%-15 wt% of the total mass of the modified suspension. Preferably, in step (1), the mass of the silicon dioxide accounts for 0.1wt%-15wt% of the total mass of the modified suspension. Preferably, in step (1), the mass ratio of the two-dimensional layered material to silicon dioxide in the modified suspension is 1:(0.1-4). Preferably, in step (1), the mass of the hydrophobic modifier accounts for 5wt%-40wt% of the total mass of the modified suspension. Preferably, in step (1), the mass of the solvent accounts for 35wt%-90wt% of the total mass of the modified suspension. Preferably, in step (2), the spray drying parameters include: the feed airflow of the modified suspension is 10-40 mm / min; the inlet temperature of the spray dryer is 90-150°C, and the inlet temperature of the spray dryer is higher than the boiling point of the solvent; the outlet temperature of the spray dryer is 70-130°C.
5. The hydrophobic composite material prepared by the method according to claim 3 or 4.
6. A 3D printing silicone rubber ink, comprising the hydrophobic composite material according to any one of claims 1 to 2 and 5, liquid silicone rubber and a curing agent. Preferably, the 3D printing silicone rubber ink comprises the following components in percentage by mass: Hydrophobic composite material 5-35wt%; Liquid silicone rubber 55-90wt%; Curing agent 5-10wt%.
7. A 3D printing silicone rubber, wherein the 3D printing silicone rubber is prepared by the 3D printing silicone rubber ink according to claim 6. Preferably, the 3D printing silicone rubber is prepared by 3D printing the 3D printing silicone rubber ink according to claim 6. Preferably, the 3D printing is direct ink writing 3D printing.
8. A 3D printing silicone rubber, wherein the raw materials for preparing the 3D printing silicone rubber include the 3D printing silicone rubber ink according to claim 6.
9. A method for preparing 3D printing silicone rubber, the method comprising the following steps: (a) Transferring 3D printing silicone rubber ink to the printing device, designing and slicing the printing model, setting printing parameters, adjusting the printing platform, and printing the desired pattern or structure; (b) heat treating the pattern or structure printed in step (a) to obtain 3D printed silicone rubber. Preferably, in step (a), the printing parameters include: The extrusion pressure is 0.4-4kgf, the extrusion speed is 0.002-0.01g / s, the printing layer height is 0.2-0.8mm, and the platform spacing is 0.2-0.8mm. Preferably, in step (b), the heat treatment is carried out by gradient heating, the temperature of the first heating stage is 80-100°C, and the heating time of the first heating stage is 20-60min; the temperature of the second heating stage is 120-150°C, and the heating time of the second heating stage is 10-30min.
10. Use of the 3D printing silicone rubber according to claim 8, which is used in the fields of electromagnetic wave absorption and thermal management.